Comparison of allergenicity among cow, goat, and horse milks using a murine model of atopy. Issue 12 (14th May 2021) - Duan, Cuicui; Ma, Lin; Cai, Lin; Li, Xiaolei; Ma, Fumin; Chen, Junliang; Huo, Guicheng; Li, Dan
Abstract : Systematic and comprehensive study on the differences of allergenicity among cow milk, goat milk, and horse milk. Abstract : Due to the prevalence and severity of cow milk (CM) allergy (CMA), an ideal substitute is urgently needed to develop hypoallergenic infant formula for infants who experience anaphylaxis to typical whey-based CM formula. Goat milk (GM) and horse milk (HM) are considered appropriate substitutes; however, whether GM and HM are less allergenic than CM is unclear. In the present study, the difference in allergenicity among CM, GM, and HM was investigated using the Balb/c mouse model. The number of mice with severe respiratory symptoms was significantly lower in the GM- and HM-sensitised groups than in the CM-sensitised group. Furthermore, histologic examination of intestinal and lung tissues revealed a thinner lamina propria of the small intestine and obvious inflammation and congestion in lungs in the CM-sensitised group than in the GM- and HM-sensitised groups. CM-specific immunoglobulin (Ig) E, serum IgG1, and plasma histamine levels were also higher in CM-sensitised mice than in GM- or HM-sensitised mice. In addition, higher interleukin (IL) 4 and IL-17A levels and lower interferon-γ (IFN-γ) and IL-10 levels were observed in CM-sensitised mice compared with GM- and HM-sensitised mice, according to qPCR, indicating Th1/Th2 and Treg/Th17 imbalances. The CM-sensitised group had a higher proportion of IL-4- and IL-17A-producing CD 3+ T cells but a lower proportion of IFN-γ- and IL-10-producing CD 3+ T cells compared with the GM- and HM-sensitised groups, confirming the Th1/Th2 and Treg/Th17 imbalances. In conclusion, GM and HM were less allergenic than CM in mice as a result of a shift in the Th1/Th2 and Treg/Th17 imbalances; however, HM was less allergenic than GM and can be used as an alternative milk to develop infant formulas for children with CMA.